2016
DOI: 10.1007/s12011-016-0874-1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Reduces Early Signs of Tumor Necrosis Factor Alpha-Induced Meniscal Tissue Degradation

Abstract: Meniscal integrity is a prerequisite for sustained knee joint health and prevention of meniscal degeneration is a main research goal. Cartilage-protective effects of selenium have been described, but little is known about the impact on the meniscus. We therefore investigated the influence of sodium selenite on meniscal explants under tumor necrosis factor-alpha (TNFα)-stimulated proinflammatory conditions. Meniscal explant disks (3 mm diameter × 1 mm thickness) were isolated from 2-year-old cattle and incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Nitric oxide can reduce autophagy by down-regulating the JNK signaling pathway, thereby affecting meniscal repair and causing meniscal degeneration 22 . Hyaluronic acid, selenium, and interleukin-10 delay or improve meniscus degeneration due to the inhibition of nitric oxide [23][24][25] . This study showed that the upregulated biological processes included regulation of nitric oxide biosynthesis process, nitric oxide biosynthetic process, and nitric oxide metabolic process, indicating that nitric oxide plays an important role in meniscal degeneration.…”
Section: Slc2a4//tmprss15//il2rg//igf2r//npy2r//cyp2c33//cyp4a21//adimentioning
confidence: 99%
“…Nitric oxide can reduce autophagy by down-regulating the JNK signaling pathway, thereby affecting meniscal repair and causing meniscal degeneration 22 . Hyaluronic acid, selenium, and interleukin-10 delay or improve meniscus degeneration due to the inhibition of nitric oxide [23][24][25] . This study showed that the upregulated biological processes included regulation of nitric oxide biosynthesis process, nitric oxide biosynthetic process, and nitric oxide metabolic process, indicating that nitric oxide plays an important role in meniscal degeneration.…”
Section: Slc2a4//tmprss15//il2rg//igf2r//npy2r//cyp2c33//cyp4a21//adimentioning
confidence: 99%